ASSESSMENT OF TOURISTS’ PERCEPTION AND SATISFACTION IN AGODI PARK AND GARDENS IBADAN AS A NATURE-BASED TOURISM ATTRACTION - Operinde, Olayinka Helen; Praise, Emma-Egoro (International Journal of Research -GRANTHAALAYAH, 2020)
This study hinges on the assessment of tourists perception and satisfaction in Agodi Park and Gardens Ibadan as a nature-based tourism attraction. The study was conducted to investigate and assess the level of tourist’s satisfaction with the attributes (facilities and services) at the Park. In order to achieve the aim of this study, a well-structured questionnaire was drafted in line with the research objectives. The findings of the study revealed that the most satisfying features at the Park was the natural environment and the swimming pool at 62.8% and 34.9% respectively. However, the most dissatisfying features were the Zoo (54.6%) and the inadequate recreational facilities (17.4). The results also shows that the quality of tourism services has a positive impact on the level of tourist satisfaction. These results are considered to be valuable to destination managers, tourism organizations and businesses in evaluating the level of their current services. Therefore, this study suggests that visitors’ satisfaction can be boosted by raising the standard of service quality throughout the destinations’ attractions, facilities and modes of accessibility. The Parks’ management should upgrade the zoological garden to meet up with International standard so as to increase tourists’ patronage and satisfaction.